Model assess the impact of the chemical composition of the conductive veins on the operational characteristics of an isolated electrical wire - Katunin, Albert; Kolomiitsev, Oleksii; Kulakov, Oleg; Panchenko, Volodymyr; Oliinyk, Ruslan; Kozhushko, Mykola (Державний науково-дослiдний iнститут випробувань і сертифікації озброєння та військової техніки, 2025)
The influence of the chemical composition of the conductive core of an insulated electric wire with single-layer isolation on its heating temperature depending on the operating time at different load currents is investigated. An improved mathematical model was used, which allows us to estimate the temperature increase of a single-core electric wire with the time of operation. The calculations were carried out using computer equipment in the MATHCAD software package for a copper conductor with impurities of iron, cobalt, and manganese in different proportions. For example, the temperature-time dependences for the PVC1 2.5 (H05V-U 2.5) electric wire were built for load currents less than, equal to, and greater than the maximum permissible values. The analysis of the obtained temperature-time characteristics made it possible to state that the heating temperature of electric wires during their operation is significantly determined by the impurity material of the copper conductor. The paper shows that the temperature-time characteristics of PVC1 2,5 (H05V-U 2,5) electric wires with different materials of copper conductor impurities have approximately the same nonlinear character at load currents of 20, 30 and 40 A. The simulation results show that for materials of iron, cobalt, manganese impurities to copper, the highest heating temperature for load currents of 20, 30 and 40 A is achieved by electric wires PVC1 2,5 (H05V-U 2,5) with an iron impurity, and the lowest - with a manganese impurity. It is shown that the heating temperature of an electric wire depends significantly on the number of impurities in the conductor material - as the number of impurities increases, the temperature rises. Therefore, the heating temperature of electric wires with different volumes of impurities in the conductor material will differ significantly. At the same time, a tendency was observed to increase the difference between the heating temperatures of electric wires with an increase in the volume of various impurities in the materials of conductive cores for all values of the load current. It was concluded that modeling allows to determine the time during which PVC1 2.5 (H05V-U 2.5) electric wires with various impurities in the conductor material heat up to critical temperatures. Досліджено вплив хімічного складу струмопровідної жили ізольованого електричного проводу з одношаровою ізоляцією на температуру його нагріву в залежності від часу роботи при різних струмах навантаження. Використано вдосконалену математичну модель, яка дозволяє оцінити підвищення температури одножильного електричного проводу з часом експлуатації. Розрахунки проведено із використанням комп’ютерного пакету програм MATHCAD для мідного провідника з домішками заліза, кобальту та марганцю в різних співвідношеннях. Для прикладу побудовані температурно-часові характеристики електричного проводу ПВХ1 2,5 (H05V-U 2.5) для струмів навантаження, менших, рівних і більших гранично допустимих значень. Аналіз отриманих температурно-часових характеристик дозволив стверджувати, що температура нагрівання електричних проводів під час їх експлуатації суттєво визначається домішковим матеріалом в мідному провіднику. У статті показано, що температурно-часові характеристики електричного проводу ПВХ1 2,5 (H05V-U 2.5) з різними матеріалами домішок в мідному провіднику мають приблизно однаковий нелінійний характер при навантаженні 20, 30 і 40 А. Результати моделювання свідчать, що для мідного провідника з домішками заліза, кобальту, марганцю найвищу температуру нагріву при струмах навантаження 20, 30 і 40 А досягають електричні проводи ПВХ1 2,5 (H05V-U 2.5) з домішкою заліза, а найнижчу – з домішкою марганцю. Показано, що температура нагріву електричного проводу суттєво залежить від об’єму домішок до матеріалу струмопровідної жили – зі збільшенням об’єму домішок температура підвищується. Тому, температура нагріву електричних проводів з різними об’ємами домішок до матеріалу струмопровідних жил буде суттєво відрізнятися. При цьому, відмічається тенденція до збільшення різниці між температурами нагріву електричних проводів при підвищенні об’ємів різних домішок до матеріалів струмопровідних жил для усіх значень струму навантаження. Зроблено висновок, що моделювання дозволяє визначати час, протягом якого електричні проводи PVC1 2.5 (H05V-U 2.5) з різними домішками в матеріалі провідника нагріваються до критичних температур.
Модель оцінки впливу хімічного складу струмовідних жил на експлуатаційні характеристики ізольованого електричного проводу
Keywords: current loading; electrical wire; intensity of heating; material of electrical core; material of the isolation; електричний провід; інтенсивність нагрівання; матеріал електричної жили; матеріал ізоляції; струмове навантаження